Thermodynamics and Energy Engineering - Vizureanu, Petrică (IntechOpen, 2020)
This book is a primary survey of basic thermodynamic concepts that will allow one to predict states of a fuel cell system, including potential, temperature, pressure, volume and moles. The specific topics explored include enthalpy, entropy, specific heat, Gibbs free energy, net output voltage irreversible losses in fuel cells and fuel cell efficiency. It contains twelve chapters organized into two sections on "Theoretical Models" and "Applications." The specific topics explored include enthalpy, entropy, specific heat, Gibbs free energy, net output voltage irreversible losses in fuel cells and fuel cell efficiency.